Dermatophilosis in cattle in Malaysia: report of two cases - Omar, Abdul Rahman; Joseph, P. G.; Anwar, M. (Persatuan Doktor Veterinar Malaysia, 1980)

(untitled)
A skin condition from sohich Dermatophilus congolensis was isolated an culture is described in t100 borine animals. This constituted the first authenticated cases of dermatophilosis in Malaysia.